Foreign Diversification of Philippine Firms - Rodriguez, Rafael A.; Sandoval, Benjamin C. (Philippine Management Review, 2016)
The paper catalogues listed Philippine companies that have either expanded operations into foreign markets or announced plans to do so. The paper uses both newspaper accounts and company disclosures to the Philippine Stock Exchange as sources of information on foreign diversification. The paper finds that for the large majority of the companies in the study, diversification moves—both planned and actual—occurred only in the last five years. More recently, these moves are in the direction of ASEAN and neighboring East Asian countries, are in the same lines of business as in the Philippines, are undertaken by companies belonging to the largest business groups in the Philippines, and exclude banks.